2012
DOI: 10.1016/j.jcmg.2011.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Plaque Composition, Morphology, and Outcomes in Patients With and Without Chronic Kidney Disease Presenting With Acute Coronary Syndromes

Abstract: Following percutaneous coronary intervention of all culprit lesions in ACS, patients with versus without CKD have more extensive and severe atherosclerosis remaining in their coronary tree with plaque composed of greater necrotic core and less fibrous tissue. These influences resulted in nonsignificantly different rates of non-culprit lesion-related adverse events, although cardiac death, arrest, or myocardial infarction were more common in patients with CKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
64
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(68 citation statements)
references
References 38 publications
(39 reference statements)
4
64
0
Order By: Relevance
“…First, CKD accompanies accelerated and extensive atherosclerosis 28. Extensive subclinical coronary atherosclerosis in CKD patients might cause unpredictable progression of lesions that were not detected on angiography alone at the index procedure, and may affect the incidence of any revascularization, irrespective of angiographic CR and IR.…”
Section: Discussionmentioning
confidence: 99%
“…First, CKD accompanies accelerated and extensive atherosclerosis 28. Extensive subclinical coronary atherosclerosis in CKD patients might cause unpredictable progression of lesions that were not detected on angiography alone at the index procedure, and may affect the incidence of any revascularization, irrespective of angiographic CR and IR.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Third, atherosclerotic plaques in patients with CKD are characterized by increased amounts of necrotic core and decreased fibrous volume, potentially enhancing plaque vulnerability. 30 In aggregate, findings of excess thrombotic risk in the absence Although it is well established that both ischemic and bleeding complications are high among patients with CKD after PCI, a novel finding from this study is that this risk is not uniform but varies substantially by the presence or absence of HPR. We found that the associations between HPR and clinical events were similar in magnitude and direction among those with and without CKD with no evidence of interaction.…”
Section: Discussionmentioning
confidence: 55%
“…21 The pathophysiology in ACS patients with underlying renal dysfunction has been studied 22 Lesions in the coronaries of patients with renal dysfunction were found to be longer with more luminal encroachment and have higher plaque burden compared to coronaries of non renal dysfunction patients. Coronary plaque composition assessed with radio frequency IVUS depicted greater necrotic core with dense calcium and less fibrous tissue, all these changes make the coronary plaque less stable.…”
Section: Discussionmentioning
confidence: 99%